2016
DOI: 10.1002/hbm.23308
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances cognitive control of food craving in women

Abstract: In developed countries, obesity has become an epidemic resulting in enormous health care costs for society and serious medical complications for individuals. The homeostatic regulation of food intake is critically dependent on top-down control of reward-driven food craving. There is accumulating evidence from animal studies that the neuropeptide oxytocin (OXT) is involved in regulating hunger states and eating behavior, but whether OXT also contributes to cognitive control of food craving in humans is still un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 70 publications
(120 reference statements)
5
64
0
1
Order By: Relevance
“…In addition, the preferential effects of intranasal administration of oxytocin in reducing consumption of more palatable foods, such as fats and carbohydrates, by men 51,52,76 is consistent with the concept that oxytocin might inhibit food intake in part by modulating reward-related food motivation and/or impulse control neurocircuitry. This concept is in line with a study published in 2016 showing that a single intranasal dose of 24 IU oxytocin increased activation of brain circuitry involved in cognitive control (detected using fMRI) and, at the trend level, reduced food craving when women were asked to cognitively control the urge to eat while viewing images of palatable foods 80 . This finding is also consistent with animal studies demonstrating that administration of oxytocin to the VTA 56 or nucleus accumbens 81 , which are regions of the brain involved in reward that receive oxytocin projections from the PVN 4 and express oxytocin receptors 23-25 , inhibits sucrose intake.…”
Section: Eating Behavioursupporting
confidence: 87%
“…In addition, the preferential effects of intranasal administration of oxytocin in reducing consumption of more palatable foods, such as fats and carbohydrates, by men 51,52,76 is consistent with the concept that oxytocin might inhibit food intake in part by modulating reward-related food motivation and/or impulse control neurocircuitry. This concept is in line with a study published in 2016 showing that a single intranasal dose of 24 IU oxytocin increased activation of brain circuitry involved in cognitive control (detected using fMRI) and, at the trend level, reduced food craving when women were asked to cognitively control the urge to eat while viewing images of palatable foods 80 . This finding is also consistent with animal studies demonstrating that administration of oxytocin to the VTA 56 or nucleus accumbens 81 , which are regions of the brain involved in reward that receive oxytocin projections from the PVN 4 and express oxytocin receptors 23-25 , inhibits sucrose intake.…”
Section: Eating Behavioursupporting
confidence: 87%
“…We predicted that LSG surgery would result in decreased FCD in regions, implicated in impaired self-control and self-referential processing (Northoff et al, 2006;Striepens et al, 2016) (VMPFC, DMPFC, precuneus), memory (HIPP), and interoception (insula), increasing connectivity of self-referential processing regions with regions involved with executive function/self-regulation (DLPFC, caudate). We predicted that LSG surgery would result in decreased FCD in regions, implicated in impaired self-control and self-referential processing (Northoff et al, 2006;Striepens et al, 2016) (VMPFC, DMPFC, precuneus), memory (HIPP), and interoception (insula), increasing connectivity of self-referential processing regions with regions involved with executive function/self-regulation (DLPFC, caudate).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we have found that in the absence of social support, intranasal OXT may produce detrimental effects and enhance the subjective experience of psychosocial stress (Eckstein et al, 2014). Additionally, OXT strengthens top-down cognitive control strengthens top-down cognitive control by enhancing activity in the middle frontal gyrus (MFG) (Eckstein et al, 2015;Striepens et al, 2016). Additionally, OXT strengthens top-down cognitive control strengthens top-down cognitive control by enhancing activity in the middle frontal gyrus (MFG) (Eckstein et al, 2015;Striepens et al, 2016).…”
mentioning
confidence: 99%